PENGARUH PENDAPATAN, PENGETAHUAN TENTANG AKAD PEMBIAYAAN SYARIAH, DAN PROMOSI BANK SYARIAH TERHADAP KEPUTUSAN MENGGUNAKAN PRODUK PEMBIAYAAN HUNIAN SYARIAH BERBASIS AKAD MURABAHAH - Amien, Muhammad Ibnu; Noor, Iswan (Islamic Economics and finance in Focus, 2022)
The purpose of this research are to find out whether the income of teachers and employees of MAN 2 and 3 Pekanbaru City, knowledge of teachers and employees of MAN 2 and 3 Pekanbaru City, and the promotion of Syariah Bank have a significant positive effect on the decision in using Islamic residential financing products based on murabahah contracts. The type of research applied is quantitative research, research data is presented in the form of numbers and performs calculations using statistical methods. The objects in this research are teachers and employees at MAN 2 and 3, totaling 104 samples to represent the 141 population. Based on the results of the research, it can be found that the independentvariables consisting of income, knowledge and promotion have an effect on the decision in using Syariah House Ownership Credit. The independent variable that has the most influence on the decision in using Syariah House Ownership Credit is the knowledge variable. Through this research, it is hoped that consumer can better understand the offers from banks regarding financing services so that it is easier to make decisions on the use of Syariah House Ownership Credit provided by Syariah Bank.